Three Novel Mutations in the NPHS1 Gene in Vietnamese Patients with Congenital Nephrotic Syndrome - Thi Kim Lien Nguyen; Van Dem Pham; Thu Huong Nguyen; Trung Kien Pham; Thi Quynh Huong Nguyen; Huy Hoang Nguyen (Case Reports in Genetics)
Congenital nephrotic syndrome, a rare and severe disease, is inherited as an autosomal recessive trait. The disease manifests shortly after birth and occurs predominantly in families of Finnish origin but has now been observed in all countries and races. Mutations in the NPHS1 gene, which encodes nephrin, are the main causes of congenital nephrotic syndrome in patients. In this study, we report the first mutational analysis of the NPHS1 gene in three unrelated children from three different Vietnamese families. These patients were examined and determined to be suffering from congenital nephrotic syndrome in the Department of Pediatrics, Vietnam National Hospital of Pediatrics. All 29 exons and exon-intron boundaries of NPHS1 were analyzed by PCR and DNA sequencing. Genetic analysis of the NPHS1 gene revealed one compound heterozygous variant p.Glu117Lys, one heterozygous missense mutation p.Asp310Asn, and one heterozygous frame-shifting mutation (c.3250_3251insG causing p.Val1084Glyfs⁎12) in patient 1. In patient 2, one heterozygous variant p.Glu117Lys and one novel heterozygous missense mutation p.Ser324Ala were identified. Finally, a novel missense mutation p.Arg802Leu and a novel nonsense mutation (c.2442C>G causing p.K792⁎) were identified in patient 3.